2017
DOI: 10.1016/j.molp.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis MADS-Box Transcription Factor AGL21 Acts as Environmental Surveillance of Seed Germination by Regulating ABI5 Expression

Abstract: Seed germination is a crucial checkpoint for plant survival under unfavorable environmental conditions. Abscisic acid (ABA) signaling plays a vital role in integrating environmental information to regulate seed germination. It has been well known that MCM1/AGAMOUS/DEFICIENS/SRF (MADS)-box transcription factors are key regulators of seed and flower development in Arabidopsis. However, little is known about their functions in seed germination. Here we report that MADS-box transcription factor AGL21 is a negative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 65 publications
0
50
0
1
Order By: Relevance
“…A number of genes have been found to respond to the environmental stresses and regulate seed germination by integrating the environmental signals to ABA signaling (Vishal & Kumar, 2018). In this study, we found that ANR1 , like AGL21 (Yu et al, 2017), also responds to multiple environmental signals, and may act as another environmental surveillance for seed germination. As two members of the AGL17-clade MADS-box genes, ANR1 and AGL21 play similar functions during root development as well as seed germination.…”
Section: Discusstionmentioning
confidence: 64%
See 2 more Smart Citations
“…A number of genes have been found to respond to the environmental stresses and regulate seed germination by integrating the environmental signals to ABA signaling (Vishal & Kumar, 2018). In this study, we found that ANR1 , like AGL21 (Yu et al, 2017), also responds to multiple environmental signals, and may act as another environmental surveillance for seed germination. As two members of the AGL17-clade MADS-box genes, ANR1 and AGL21 play similar functions during root development as well as seed germination.…”
Section: Discusstionmentioning
confidence: 64%
“…ANR1 integrates multiple environmental signals and developmental information to determine the proper timing for seed germination by directly regulating ABI3 expression. The ANR1-ABI3 signaling module, together with previously reported AGL21-ABI5 module (Yu et al, 2017), forms a safeguard mechanism that double ensures seeds to germinate at right time and under favorable conditions.…”
Section: Discusstionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, some genes that positively or negatively regulate ABI5 transcription have been identified. For example, ABI4, HY5, SPT (SPATULA) and AGL21 positively regulate transcription of ABI5 (Chen et al, 2008;Bossi et al, 2009;Vaistij et al, 2013;Yu et al, 2017), and, notably, ABI5 can activate ABI5 expression (Xu et al, 2014). Among them, SPT and ABI5 are able to bind the G-box element in ABI5 promoter, whereas other positive regulators occupy different regions of the ABI5 promoter through other cis elements (Chen et al, 2008;Bossi et al, 2009;Vaistij et al, 2013;Yu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, ABI4, HY5, SPT (SPATULA) and AGL21 positively regulate transcription of ABI5 (Chen et al, 2008;Bossi et al, 2009;Vaistij et al, 2013;Yu et al, 2017), and, notably, ABI5 can activate ABI5 expression (Xu et al, 2014). Among them, SPT and ABI5 are able to bind the G-box element in ABI5 promoter, whereas other positive regulators occupy different regions of the ABI5 promoter through other cis elements (Chen et al, 2008;Bossi et al, 2009;Vaistij et al, 2013;Yu et al, 2017). Several negative regulators of ABI5 were also identified, including WRKY40, RAV1 (Related to ABI3/VP1), BRM (ATPase BRAHMA) and BBX21 (Shang et al, 2010;Han et al, 2012;Feng et al, 2014;Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%